Adverse events following immunization in pregnant women from Minas Gerais - Isabela Oliveira da Silveira; Thales Philipe Rodrigues da Silva; Bianca Maria Oliveira Luvisaro; Roberta Barros da Silva; Josianne Dias Gusmão; Aline Mendes Vimieiro; Valéria Conceição de Oliveira; Karina Cristina Rouwe de Souza; Ana Paula Vieira Faria; Fernanda Penido Matozinhos (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To analyze the distribution of adverse events following immunization (AEFI) in pregnant women in the state of Minas Gerais, between 2015 and 2019. METHODS: This is an epidemiological, descriptive study conducted with AEFI data from 2015 to 2019, recorded in the Adverse Events Surveillance Information System, in the state of Minas Gerais (MG), Brazil. A total of 670 AEFI were analyzed in pregnant women. The estimates were presented in proportions, according to the year of occurrence, health macro-region of Minas Gerais and immunobiological administered. RESULTS: The year in which there were the most records was 2017 (36.8%). Among the 14 macro-regions, the ones with the lowest and highest number of records were the Vale do Jequitinhonha (0.5%) and Center (31.8%), respectively. The vaccines contraindicated during pregnancy represented 27.6% of the total notifications. The total of 69.5% of the cases were considered immunization errors. In 75.9% of the records, the variable of medical care was ignored, and in 73.7% of the cases no information on the evolution was presented. CONCLUSION: This study shows the need for continuing education for the multidisciplinary team, in order to reduce cases of AEFI and ensure the adequate completion of notifications by health professionals.